2018
DOI: 10.1001/jamanetworkopen.2018.1851
|View full text |Cite
|
Sign up to set email alerts
|

Association of Race and Ethnicity With Glycemic Control and Hemoglobin A1c Levels in Youth With Type 1 Diabetes

Abstract: Key Points Question Is there evidence for racial/ethnic health inequity with respect to longitudinal patterns of glycemic control among youth with type 1 diabetes? Findings In a longitudinal cohort study of 1313 youths (aged <20 years) with type 1 diabetes, patients with black race or Hispanic ethnicity were at higher risk of being in the highest and most rapidly increasing hemoglobin A 1c trajectory group over 9 years after diabe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
41
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(57 citation statements)
references
References 72 publications
(95 reference statements)
5
41
1
Order By: Relevance
“…Alhough we were able to obtain HbA 1c levels one‐year post‐baseline, the DSSE and Self‐Care Inventory scores were only obtained at baseline, limiting our ability to examine how changes in these factors could have predicted changes in glycaemic control or the direction of these effects. Additionally, factors such as age, race/ethnicity and duration of illness were not significantly associated with self‐care or glycaemic control, contrary to previous research . While the homogeneity and small sample size may have made differences among groups or of moderating effects difficult to detect, the role of race/ethnicity should continue to be examined.…”
Section: Discussioncontrasting
confidence: 64%
See 1 more Smart Citation
“…Alhough we were able to obtain HbA 1c levels one‐year post‐baseline, the DSSE and Self‐Care Inventory scores were only obtained at baseline, limiting our ability to examine how changes in these factors could have predicted changes in glycaemic control or the direction of these effects. Additionally, factors such as age, race/ethnicity and duration of illness were not significantly associated with self‐care or glycaemic control, contrary to previous research . While the homogeneity and small sample size may have made differences among groups or of moderating effects difficult to detect, the role of race/ethnicity should continue to be examined.…”
Section: Discussioncontrasting
confidence: 64%
“…Furthermore, age and race/ethnicity have been shown to significantly impact overall diabetes care. Adolescence has long been identified as a developmental stage during which glycaemic control and self‐care worsen , but research has shown that ethnic‐minority status significantly increases the probability of poor self‐care and glycaemic control . Increasing knowledge about the relationship between self‐esteem and diabetes management in a high‐risk group has the potential to further increase our understanding of the decline in self‐care and glycaemic control, as well as to inform future research and interventions for providers who work with those adolescents who are struggling to maintain optimal control from a physical and emotional perspective.…”
Section: Introductionmentioning
confidence: 99%
“…Race/ethnicity is likely a surrogate for other important unmeasured variables, which might include biopsychosocial factors like genetic risk, provider and family perceptions of treatment intensity, or access to care . Racial/ethnic disparities in insulin pump use, complications, and treatment outcomes have been widely reported in youth with T1D, including recently in the SEARCH for Diabetes in Youth study, and there is a clear need for novel strategies to close this gap.…”
Section: Discussionmentioning
confidence: 99%
“…By the year 2050, demographic and incidence trends suggest that there will be a three‐to‐seven‐fold increase in the number of Latino youth with T1DM (Imperatore et al, 2012). Compared to White youth, Latino youth with T1DM have higher rates of elevated glycated hemoglobin (A1C) levels (Kahkoska et al, 2018; Petitti et al, 2009; Willi et al, 2015), placing them at greater risk of serious health consequences (Carlsen et al, 2017; Diabetes Control and Complications Trial Research Group, 1994; White et al, 2001). As the number of Latino youth with T1DM grows, so does the need to improve resources and care for Latino families to support self‐management and adaptation to T1DM.…”
Section: Introductionmentioning
confidence: 99%